The Influence of System Quality, Information Quality, and Service Quality on User Satisfaction of the M-Passport Application at the Class I TPI Bandar Lampung Immigration Office - Putri Rachma Sholeha; Yulianto, Yulianto; Ahmad Rifa’i (Cita konsultindo, 2025)
In today's digital era, information technology plays an important role in improving the quality of public services. One of the innovations implemented by the Class I TPI Bandar Lampung Immigration Office is the use of the M-Passport application to facilitate the online passport application process. This study aims to analyze the effect of system quality, information quality, and service quality on the satisfaction of M-Passport application users at the Class I TPI Bandar Lampung Immigration Office. The method used in this study is a survey with a quantitative approach. Specifically, system quality has a strong influence on user satisfaction, followed by information quality and service quality. Positive assessments of system quality, information, and service indicate that the M-Passport application has met user needs in terms of reliability, ease of use, and response speed. Thus, this study concludes that in order to improve user satisfaction of the M-Passport application, the Class I TPI Bandar Lampung Immigration Office needs to continue to improve the quality of the system, information, and services provided. This study is expected to provide insight for M-Passport application managers and related agencies in efforts to improve public services based on information technology.